Philosophy of Technology
XXIV, 192 p.
Keywords: The corps of philosophers who make up the Society for Philosophy & Technology has now been collaborating, in one fashion or another, for almost fifteen years. In addition, the number of philosophers, world-wide, who have begun to focus their analytical skills on technology and related social problems grows increasingly every year. {It would certainly swell the ranks if all of them joined the Society!) It seems more than ap propriate, in this context, to publish a miscellaneous volume that em phasizes the extraordinary range and diversity of contemporary contribu tions to the philosophical understanding of the exceedingly complex phenomenon that is modern technology. My thanks, once again, to the anonymous referees who do so much to maintain standards for the series. And thanks also to the secretaries - Mary Imperatore and Dorothy Milsom - in the Philosophy Department at the University of Delaware; their typing and retyping of the MSS, and especially notes and references, also contributes to keeping our standards high. PAUL T. DURBIN vii Paul T. Durbin (ed.), Philosophy ofT echnology, p. vii.